A plug-and-play system for polycyclic tetramate macrolactam production and functionalization - Anna Glöckle; Sebastian Schuler; Manuel Einsiedler; Tobias A. M. Gulder (Microbial Cell Factories)
Abstract Background The biosynthesis of the natural product family of the polycyclic tetramate macrolactams (PoTeMs) employs an uncommon iterative polyketide synthase/non-ribosomal peptide synthetase (iPKS/NRPS). This machinery produces a universal PoTeM biosynthetic precursor that contains a tetramic acid moiety connected to two unsaturated polyene side chains. The enormous structural and hence functional diversity of PoTeMs is enabled by pathway-specific tailoring enzymes, particularly cyclization-catalyzing oxidases that process the polyene chains to form distinct ring systems, and further modifying enzymes. Results Ikarugamycin is the first discovered PoTeM and is formed by the three enzymes IkaABC. Utilizing the iPKS/NRPS IkaA, we established a genetic plug-and-play system by screening eight different strong promoters downstream of ikaA to facilitate high-level heterologous expression of PoTeMs in different Streptomyces host systems. Furthermore, we applied the system on three different PoTeM modifying genes (ptmD, ikaD, and cftA), showing the general utility of this approach to study PoTeM post-PKS/NRPS processing of diverse tailoring enzymes. Conclusion By employing our plug-and-play system for PoTeMs, we reconstructed the ikarugamycin biosynthesis and generated five derivatives of ikarugamycin. This platform will generally facilitate the investigation of new PoTeM biosynthetic cyclization and tailoring reactions in the future.